A Future Study on the Adoption of Hologram Traffic Light for Reducing Accidents in Malaysia - Rafiuddin Afkari, Zulfana Lidinillah; Siti Aisyah Salim (Research in Management of Technology and Business, 2023)
Three-dimensional hologram is a system that consists of a virtual holographic wall that can reduce reckless drivers at traffic lights. The concept is based on a laser projector that only shows images of moving pedestrians, visible with a light red-light laser to drivers in front of it. Even with regular traffic lights, it is impossible to reduce traffic accidents. The current study is also focused on road users how to reduce accident, and there is still a lack of research on the following perspectives of hologram traffic lights in Malaysia. Due to the increasing number of vehicles on the highway, the function of traffic lights is critical, and their presence isrequired to maintain traffic order. When driving, the driver must pay attention to the color of the traffic lights. Hence, this research aims to identify the level of road users to maintain the safety of pedestrians and vehicles if we use hologram traffic lights in Malaysia. Furthermore, holographic traffic lights will aid communication between vehicles and pedestrians in high- risk regions. The sample was gathered using a quantitative research method that included a self-administered questionnaire and an internet survey. All of the gathered data was examined using the Statistical Package for Social Science (SPSS) to create quantitative results in frequency, percentage, mean and standard deviation. These study research ways to decrease accidents by employing hologram traffic lights for drivers.